Bess for Energy Arbitrage and Ancillary Services: The Case of Chile - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2019)
The contribution of Battery Energy Storage System (BESS) to power system operation is currently widely accepted. Aspects such as fast response has an important impact on system adequacy. However, it is not clear if BESS are economically sustainable, given the high investment costs and the various regulatory frameworks in different countries. This work presents a detailed analysis on the particular case of Chile to understand BESS economic opportunities. In particular, energy arbitrage and ancillary services are considered. © 2019 IEEE.